2006
DOI: 10.1080/00365590500368922
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of zinc levels in benign and malignant lesions of the prostate

Abstract: There appears to be a strong correlation between plasma zinc levels and various prostatic diseases. Therefore, the determination of zinc levels can be used as a diagnostic or screening tool and may lead to the formulation of methods in which zinc is used to evaluate prostatic pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 12 publications
1
21
0
1
Order By: Relevance
“…Although low plasma zinc concentrations have been reported in patients with prostate carcinoma (0.6+/−0.03 μg/ml in patients with prostatic malignancies vs. 0.95+/−0.1 μg/ml in healthy controls), 38 this is not the likely culprit for a decreased zinc accumulation in malignant prostate cells. Instead, prostate cancer modulates the specialized mechanisms that are required for both zinc uptake and release.…”
Section: Zinc Transportmentioning
confidence: 83%
“…Although low plasma zinc concentrations have been reported in patients with prostate carcinoma (0.6+/−0.03 μg/ml in patients with prostatic malignancies vs. 0.95+/−0.1 μg/ml in healthy controls), 38 this is not the likely culprit for a decreased zinc accumulation in malignant prostate cells. Instead, prostate cancer modulates the specialized mechanisms that are required for both zinc uptake and release.…”
Section: Zinc Transportmentioning
confidence: 83%
“…Although serum Zn levels are considered a poor indicator of Zn status, serum Zn levels are generally low in patients with multiple cancers [30], including patients with squamous esophageal cancer [31], malignant prostate cancer [32], ovarian cancer [33], and cancers of the gallbladder [34], lung [35], colon, head and neck [36], and bronchus [35]. Multiple studies also show a relationship between low plasma Zn levels and the risk for developing breast cancer [37,38,39], prompting the suggestion that plasma Zn levels can be used as a prognostic as well as a therapeutic marker for breast cancer [40,41,42].…”
Section: Comparative Plasma and Tumor Zinc Levels And Breast Cancementioning
confidence: 99%
“…There was a highly statistically significant difference in plasma Zinc level between patients with benign and malignant prostatic disease. 5 The effect of metastasis of carcinoma of the prostate on plasma Zinc levels was not significant(p>0.05). They concluded that determination of serum zinc levels can be used as a diagnostic and screening tool and may lead to the formulation of methods in which Zinc is used to evaluate prostatic pathology.…”
Section: Methodsmentioning
confidence: 98%